Kryptosega Kimsey, 1986 (Hymenoptera, Chrysididae) is newly recorded genus from Oriental Region, with description of one new species - Li, Shuang-Shuang; Xu, Zai-Fu (Zootaxa, 2016)
The genus Kryptosega Kimsey 1986 was described in the subfamily Amiseginae with two new species, K. anomala Kimsey and K. kaindeana Kimsey from New Guinea (Kimsey 1986). Later third species K. mweramwera Villemant was described from Vanuatu (Villemant et al. 2012). The genus resembles Indothris Krombein, 1957 by having head with occipital carina, mesopleuron without scrobal sulcus, and hind coxa without dorsobasal carina, but differs from the latter by having metanotum without median enclosure, and propodeum rounded posterolaterally (Kimsey & Bohart 1991). Amiseginae are the parasites of the eggs of walking stick insects (Phasmida) and can be found in the low vegetation or leaf litter (Kimsey & Bohart 1991). However, the biology of Kryptosega is still unknown (Villemant et al. 2012).